Răspuns :
13²=(2-7)²+(1-a)²
169=25+(1-a)²
(1-a)²=144
1-a= 12 a=-11
1-a=-12 a=13
169=25+(1-a)²
(1-a)²=144
1-a= 12 a=-11
1-a=-12 a=13
[tex]AB= \sqrt{(XA-XB) ^{2} +(YA-YB) ^{2} } =13[/tex]
[tex]AB= \sqrt{(2-7) ^{2} +(1-a) ^{2} } =13[/tex]
25+(1-a)²=169
(1-a)²=144
1-2a+a²=144
a²-2a-143=0
Δ=4+572
Δ=576
√Δ=24
=>a₁=(2-24)/2=(-11)
=>a₂=(2+24)/2=26/2=13
=>B(7,-11),sau,B(7,13)
[tex]AB= \sqrt{(2-7) ^{2} +(1-a) ^{2} } =13[/tex]
25+(1-a)²=169
(1-a)²=144
1-2a+a²=144
a²-2a-143=0
Δ=4+572
Δ=576
√Δ=24
=>a₁=(2-24)/2=(-11)
=>a₂=(2+24)/2=26/2=13
=>B(7,-11),sau,B(7,13)